Energy evaluation and environmental impact assessment of transportation fuels in Pakistan. (June 2021) - Yaqoob, Haseeb; Teoh, Yew Heng; Goraya, Talha S.; Sher, Farooq; Jamil, Muhammad Ahmad; Rashid, Tazien; Yar, Kashif Allah
Abstract: The recent studies emphasize the importance of modern technologies and the reduction of gases emission while neglecting the significance of the optimum fuel. A comprehensive comparison for compressed natural gas, liquified natural gas, liquified petroleum gas, gasoline, electricity, diesel, and alternative fuels such as bioethanol and biodiesel as a transport fuel is carried out for Pakistan. The comparison is carried out by undertaking various factor that affects the fuel economy. Therefore, a comparison of fuel properties, production, consumption, emission of gases, engine performance and economy are carried to observe the optimum fuel for Pakistan. It concluded that compressed natural gas, electricity, and alternative fuels were found to be the optimum fuel for the environment and economy of Pakistan and having a high potential for its availability through different sources. Besides, strategy and future policies and directions are also discussed for the optimum fuel. Moreover, the future of vehicles is also discussed to analyze the transportation trend of the world. The present study will be very efficient for the optimum fuel consideration and growing future for developing countries. Therefore, Pakistan should pay attention to these fuels for their production, implementation, and electric vehicles for a sustainable future.